Identification Fishing Gear of Groupers Environmentally Friendly, in Gusung Island Selayar Archipelago Regency - Sajriawati Sajriawati; Astaman Amir (Musamus Fisheries and Marine Journal, 2019)
This research was conducted from March to April 2016 located on Gusung Island, Selayar Islands Regency. The research objective was to determine the diversity of types of grouper fishing gear based on environmentally friendly indicators. The study used a survey method with a case study approach, through the determination of respondents purposively and analyzed descriptively. The results of the study found 2 (two) types of environmentally friendly fishing gear namely traps and fishing rod.